Effect of supplementation with agro-industrial by-products and Khat (Catha edulis) leftovers on testicular growth and sperm production in Ogaden bucks - Mekasha, Yoseph; Tegegne, Azage; Rodríguez Martinez, H. (Wiley, 2007)
The aim of this study was to characterize growth and sperm production parameters in Ogaden bucks fed a basal diet of hay and supplemented with agro-industrial by-products and Khat leftovers in Ethiopia. Thirty-five bucks with a mean (±SD) initial live body weight (BW) of 15.5 ± 1.5 kg were randomly assigned to one of four dietary treatments for a period of 13 weeks. Treatments consisted of native hay fed ad libitum (control; C), native hay supplemented with a 1% of BW agro-industrial by-products (treatment 1; T1), native hay supplemented with Khat (Catha edulis) leftovers at a rate of 1% of BW (treatment 2; T2) and Khat leftovers fed ad libitum (treatment 3; T3). Bucks fed on T1-T3 had higher BW, body condition score, scrotal circumference (SC), testicular width and testicular length, compared to controls (P < 0.05). Also, bucks in T1-T3 had higher sperm progressive motility, sperm concentration per ml and total number of spermatozoa per ejaculate compared to controls (P < 0.05). Between treatments, bucks in T3 recorded the highest BW (17.2 ± 0.16) and testicular size (21.1 ± 0.17 cm). Both testicular and epididymal weight and dimensions were significantly affected (P < 0.05) by supplementation compared to controls. Testicular size was positively correlated to live BW (r = 0.53, P < 0.001). SC was positively correlated with ejaculate volume (r = 0.37, P < 0.001), sperm mass activity (r = 0.65, P < 0.001) and individual sperm progressive motility (r = 0.40; P < 0.001). Supplementation with Khat leftovers induced the highest improvement in live BW, testicular size, semen production and sperm motility in Ogaden bucks and can possibly be considered as a feed supplement to enhance goat production under smallholder livestock farming system in Ethiopia.